MEMBINGKAI PRINSIP PENDISIPLINAN TUHAN YESUS BERDASARKAN MARKUS 8:33 - Jon, Bong Min; Suwito, Gregorius (Shift Key : Jurnal Teologi dan Pelayanan, 2022)
This study aims to find out how the disciplinary principle of the Lord Jesus is based on Mark 8:33 and its application. The method used in this research is qualitative with the type of case study. The results of the research are that the principle of discipline includes the respondent's understanding of the meaning and importance of discipline for positive things. The purpose of discipline is the reason for regular work in the office and the lack of violations that occur. The principle of discipline carried out by the Lord Jesus is the reason for doing work in the office.